Chemistry and Bioactivity of Marine-Derived Bisabolane Sesquiterpenoids: A Review - Li, Cheng-Shou; Liu, Li-Ting; Yang, Lei; Li, Jing; Dong, Xin (Frontiers in Chemistry, 2022)
Natural products, characterized by intriguing scaffold diversity and structural complexity, as well as significant agricultural and medicinal activities, have been a valuable source of agrochemicals/drugs development and have historically made a huge contribution to pharmacotherapy. Structurally, bisabolanes are a family of naturally occurring sesquiterpenoids that featured a hexatomic ring core incorporating with eight continuous carbons, which cause high structural variability along the alkyl side chain to form abundant functionalities. Moreover, apart from their interesting structures, bisabolanes have shown multitudinous bioactivities. Bisabolanes are distributed in a variety of marine invertebrates, terrestrial plant, and microbial sources. Interestingly, bisabolanes characterized from marine environment possess unique characteristics both structurally and biologically. A total of 296 newly-discovered bisabolanes were searched. Among them, 94 members were isolated from marine organisms. This review particularly focuses on the new bisabolanes characterized from marine organisms (covering from 2000 to 2021), including marine-derived fungi, algae, soft corals, and sponges, with emphasis on the diversity of their chemical structures as well as the novelty and differences between terrestrial and marine sources. Moreover, a wide range of bioactivities of marine-derived bisabolanes, including antimicrobial, anti-inflammatory, enzyme inhibitory, and cytotoxic properties, are presented herein, which is considered to be a promising resource for the discovery of new drug leads and agrochemicals.